Variant in the RFWD3 gene associated with PATN1, a modifier of leopard complex spotting. (16th November 2015) - Holl, H. M.; Brooks, S. A.; Archer, S.; Brown, K.; Malvick, J.; Penedo, M. C. T.; Bellone, R. R.
Summary: Leopard complex spotting (LP), the result of an incompletely dominant mutation in TRPM1, produces a collection of unique depigmentation patterns in the horse. Although the LP mutation allows for expression of the various patterns, other loci are responsible for modification of the extent of white. Pedigree analysis of families segregating for high levels of patterning indicated a single dominant gene, named Pattern‐1 ( PATN1 ), as a major modifier of LP . Linkage analysis in two half‐sibling families segregating for PATN1 identified a 15‐Mb region on ECA3p that warranted further investigation. Whole transcriptome sequencing of skin samples from horses with and without the PATN1 allele was performed to identify genic SNPs for fine mapping. Two Sequenom assays were utilized to genotype 192 individuals from five LP ‐carrying breeds. The initial panel highlighted a 1.6‐Mb region without a clear candidate gene. In the second round of fine mapping, SNP ECA3:23 658 447T>G in the 3′‐UTR of RING finger and WD repeat domain 3 ( RFWD3 ) reached a significance level of P = 1.063 × 10 −39 . Sequencing of RFWD3 did not identify any coding polymorphisms specific to PATN1 horses. Genotyping of the RFWD3 3′‐UTR SNP in 54 additional LP animals and 327 horses from nine breeds not segregating for LP further supported the association ( P = 4.17 × 10 −115 ). This variant is a strong candidate for PATN1 and may be particularly useful for LP breeders to select for high levels of white patterning.